PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS KOPERASI DAN USAHA MIKRO KOTA DEPOK - Hilda Pebrina (CV. ALIM'SPUBLISHING, 2023)
This research is based on the influence of work discipline and work environment on the performance of employees of the Department of Cooperatives and Micro Enterprises of Depok City. This was done to see the level of work discipline and work environment of the Depok City Cooperatives and Micro Enterprises Department employees. The research method used is a quantitative method with a descriptive analysis approach, because it is a method used to determine the relationship and influence between two or more variables. Data collection techniques were through observation, literature study and questionnaires distributed to 62 respondents using total sampling techniques. In analyzing the data, the formula for Correlation Coefficient, Multiple Linear Regression, Coefficient of Determination, T Test and F Test was used. The research results show that the coefficient of determination value was 0.504, so it can be concluded that the Work Discipline and Work Environment variables have an effect on Employee Performance by 50.4%. while the remaining 49.6% is influenced by other variables outside this research. The conclusion from the data analysis above is that there is a positive and significant influence of work discipline and work environment on the performance of employees of the Department of Cooperatives and Micro Enterprises of Depok City. Implemented quite well so that it has improved employee performance.